Addressing the PISA 2022 Results: A Call for Reinvigorating Indonesia's Education System - Bilad, Muhammad Roil; Zubaidah, Siti; Prayogi, Saiful (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2024)
The 2022 Programme for International Student Assessment (PISA) results depict a significant decline in the academic performance of Indonesian 15-year-olds in mathematics, reading, and science. The results position Indonesia's scores among the lowest since the country first participation in 2001. This editorial examines the implications of these results, drawing on data presented in PISA 2022, which illustrate the downward trend in performance and the widening gap between different socioeconomic groups. It argues for urgent educational reforms aimed at overhauling the current curricular frameworks, enhancing teacher training, and ensuring equitable educational opportunities. Specific strategies to achieve these goals include implementing the Merdeka Curriculum to promote student-centered learning, integrating educational neuroscience-based interventions to address learning disabilities, and leveraging intelligent tutoring systems and social media for collaborative learning. Additionally, developing localized assessments like the Indonesian Madrasah Competency Assessment and the Assessment of Indonesian Student Competence ensures alignment with international standards while addressing local needs. Through a comparative analysis with OECD averages and higher-performing nations, this piece highlights the necessity for Indonesia to adopt international best practices while tailoring them to local contexts. The ultimate goal is to equip Indonesian students with the skills necessary to meet both current and future challenges, thus improving their outcomes in subsequent PISA assessments and fostering national development. This article calls on policymakers, educational leaders, and stakeholders to engage in a concerted effort to address these educational deficiencies with the seriousness they deserve.